The Implementation of the Picture and Picture Method in Teaching Arabic Vocabulary to TPQ Students at Baiturrahim Mosque, Pagar Dewa, Bengkulu City - Alvi Nurisa; Kevin Dwi Anugrah; Wilda Nurul Qodriyah; Nopesi; Arinal Haqo; Melani Masrifah Hidayah; Farhatun Nisa; Anggi Rahmadani; Akhiruddin (Walada: Journal of Primary Education, 2026)
Vocabulary is one of the essential components in Arabic language learning that supports students’ language proficiency. However, many students at TPQ experience difficulties in understanding and memorizing Arabic vocabulary. This study aims to describe the implementation of the Picture and Picture method in teaching Arabic vocabulary to students at TPQ Baiturrahim Mosque, Pagar Dewa, Bengkulu City. This research employs a descriptive qualitative approach with data collection techniques consisting of observation, interviews, and documentation. The results of the study indicate that the Picture and Picture method is implemented through the use of pictures as learning media to introduce and reinforce students’ understanding of Arabic vocabulary. The students showed positive responses because the learning process became more engaging and interactive. The application of this method also helped improve students’ comprehension and retention of Arabic vocabulary. Therefore, the Picture and Picture method can serve as an effective alternative approach in teaching vocabulary at TPQ